Application and depression mechanism of sodium sulfite on galena-pyrite mixed concentrate flotation separation: Huize Lead-Zinc Mine, China, as an example. (July 2022) - Pan, Zuchao; Liu, Zhicheng; Xiong, Jingjing; Li, Jialei; Wei, Qian; Zhang, Zhengquan; Jiao, Fen; Qin, Wenqing
Graphical abstract: Highlights: Na2 SO3 replaces a part of CaO in the galena-pyrite mixed concentrate flotation separation.. Na2 SO3 has a significant depression effect on EX-preadsorbed pyrite. Na2 SO3 can desorbed xanthate species on pyrite surface. Abstract: Galena, sphalerite, and pyrite are important metallic sulfide minerals and are often associated with one another. In the flotation separation of galena-pyrite mixed concentrate, large amounts of lime (CaO) are used for the depression of pyrite. In this study, the negative effects of lime were reduced by using an efficient depressant Na2 SO3 + CaO reagent in the flotation separation of galena from pyrite. Real ore sample flotation separation tests showed that the mixed depressant can efficiently depress pyrite from galena-pyrite mixed concentrate. The obtained galena concentrate had a Pb recovery and grade of 58.36% and 83.45%, respectively. Micro-flotation experiments showed that Na2 SO3 depressed the floatability of pyrite more strongly than that of galena. Moreover, the depression mechanism of Na2 SO3 was observed through contact angle measurements, ultraviolet–visible spectrophotometry (UV–Vis) analysis, and time of flight secondary ion mass spectrometry (TOF-SIMS). This study provides an important reference for the depression of pyrite from a galena-pyrite mixed concentrate with low lime dosage.